The function of the “Ekhoni Account (Digital Account)” offered by The City Bank & the opinions of its staff - Mehbuba, Raida (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022